PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN KOMITMEN TUJUAN TERHADAP IMPLEMENTASI ANGGARAN BERBASIS KINERJA DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMODERASI (Studi pada Satuan Kerja Badan Layanan Umum Perguruan Tinggi di Kota Malang) - Sholihah, Ria Anisatus; Rosidi, Rosidi; Purnomosidhi, Bambang (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Ria Anisatus Sholihah. 2014. The Influence of the Quality of Human Resourcesand Goal Commitment on the Implementation of Performance Based Budget-ing with Organizational Culture as Moderating Variable. Postgraduate Eco-nomics and Business Faculty of Brawijaya University. Supervisor: Rosidi. Co-Supervisor: Bambang Purnomosidhi. This research aimed to analyze the influ-ence of the quality of human resources and goal commitment on the implemen-tation of performance-based budgeting. In addition, this research aimed toanalyzes the influence of the quality of human resources and goal commitmenton the implementation of performance-based budgeting moderated by organi-zational culture. The results showed that the quality of human resources has apositive effect on the implementation of performance-based budgeting. How-ever, this study did not succeed in proving that goal commitment affects theperformance-based budget implementation. This study also failed to demon-strate empirically that organizational culture can be a moderating variable to influence of the quality of human resources and goal commitment on theimplementation of performance-based budgeting.